Perancangan Fool Proof Information System (FPIS) Untuk Meningkatkan Kinerja Pemeliharaan Mandiri (Autonomous maintenance) - Widya, Adi Rusdi; Intani, Arvita Emarilis (JURNAL TEKNIK INDUSTRI, 2020)
Designing a machine maintenance and maintenance system in a company organization is needed to improve the company's ability in business competition in the era of the Industrial Revolution 4.0, the use of IoT (Internet of things), Human Machine Interface (HMI) makes it easier to develop a machine monitoring system, one of which is to carry out the system. Machine Daily Checklist before operating the machine to carry out the production process. Sudden machine failure during the production process is the failure of the operator when doing an initial check of the machine before it is operated, the difficulty of filling the checklist machine when starting the initial check is an opportunity for the development of a method with an error prevention system (Fool Proof System) or previously with the Japanese term Poka Yoke System. The design of the Fool Proof Information System (FPIS) system is a machine checking system that is programmed using a touch screen panel before the operator runs the machine for the production process. The machine component abnormalities before the machine breakdown can be seen by the operator before starting the production process. Autonomous maintenance with FPIS can be done quickly, precisely and accurately so that the machine part life is well maintained and the production process can meet the targets set by the company organization.